Analisis Kesalahan Siswa Pada Materi Relasi Dan Fungsi Di Kelas VIII UPT SMP Negeri 1 Ranah Pesisir - Okviani Syafti; Sefrinal; Reza Alpionita (Kilau Publishing, 2024)
The purpose of study is to describe (1) the errors made by students in sloving relation and function problems in class VIII UPT SMP Negeri 1 Ranah Pesisir, (2) the causes of errors made by students in solving relations and function problems, this type of research is qualitative with a descriptive method. The subjects in this study were class VIII.2 students of SMP Negeri 1 Ranah Pesisir consisting of 6 students, namely 2 students each, with high, medium and low abilities. The instruments in this study were the researchers themselves, students error test sheets and interview guidelines. Data collection was carried out by tests and interviews. The data analysis used was 1) data reduction, 2) data presentation, 3) drawing conclusions the research results of the study showed that subjects with high abilities made only a few mistakes, subjects with medium abilities made more than one mistake and subjects with low abilities made many mistakes. The types of errors that students often make in relation and function material are in the concept, studenst do not understand the function material so that students cannot distingish between function and relations and relations. In principle, students do not remember and do not write down the function formula. Errors in operations occur because students are not careful in completing integer aritmetic operations in relation and function questions.